Iatrogenic colonic perforation by colonoscopy: outcomes of surgery at a single center - Smolskas, Edgaras; Dulskas, Audrius; Kildušienė, Inga; Stratilatovas, Eugenijus; Samalavičius, Narimantas E. (Lietuvos chirurgija, 2017)
Background Although the incidence of iatrogenic colonoscopic perforation is low, it can result in severe complications and mortality. This study assessed the incidence and surgical management outcomes of iatrogenic colonic perforations. Materials and Methods We reviewed all the medical records of patients with colonic perforations during diagnostic or therapeutic colonoscopies from January 2007 to December 2016 at National Cancer Institute. We collected the patient’s demographic data, colonoscopic reports, and data regarding the location of perforations, their treatment and outcome. Results 16 186 colonoscopies were performed at National Cancer Institute. The overall perforation rate was 0.14% (23 of 16 186). Of the total 23 colon perforations, 20 were managed operatively. The most common location was the sigmoid colon, in 12 cases. The most used surgical technique was simple suture (11 cases) followed by resection with anastomosis (6 cases). Three patients died (one because of multiple organ failure caused by acute bronchopneumonia and two patients with intra-abdominal sepsis died due cardiopulmonary insufficiency). Conclusions: If surgery and its associated morbidity can be avoided in cases of colonic perforation the negative impact of a colonoscopy-associated complication can be minimized considerably. Patients need to be informed of the complications of colonoscopy, and clinicians must be cautioned about the potential problems for patients with a high anaesthetic risk when performing the procedure.